Modelling of the Soft Shell Technique Using Computational Fluid Dynamics - Watanabe I; Mukuno H (Clinical Ophthalmology)
Ippei Watanabe,1 Hirokazu Mukuno2 1Medical Affairs, Seikagaku Corporation, Chiyoda-ku, Tokyo, Japan; 2Shinnagata Eye Hospital, Kobe, Hyogo, JapanCorrespondence: Ippei Watanabe, Medical Affairs, Seikagaku Corporation, 1-6-1 Marunouchi, Chiyoda-ku, Tokyo, 100-0005, Japan, Tel +81 3 352208595, Fax +81 3 352208975, Email ippei.watanabe@seikagaku.co.jpPurpose: To clarify how ophthalmic viscosurgical devices (OVDs) behave during the soft shell technique.Methods: We simulated the fluids dynamics of a Dispersive-OVD [Combination of 3% hyaluronic acid (HA) and 4% chondroitin sulfate] and Cohesive-OVD (1% HA with a high molecular weight) during the soft shell technique using the software program Fluent2023R2 and ICEM CFD. During the simulation, 0.1 mL of Dispersive-OVD was injected into the eye model for 9 sec, followed by 0.1 mL of Cohesive-OVD for 5 sec. The mass fraction, static pressure, velocity, shear rate and apparent viscosity of each OVD were evaluated during intraocular injection.Results: Initially, the Dispersive-OVD was injected upward into the anterior chamber. Although the pressure applied to the cannula tip during injection was high, almost no pressure rise occurred inside the eye. Subsequently, injection of Cohesive-OVD pushed the Dispersive-OVD up, forming a thin layer of Dispersive-OVD covering the entire corneal endothelium. Injection of Cohesive-OVD increased the velocity magnitude towards the eye incision; once the OVD filled the eye, it overflowed from the incision. The shear rate of Cohesive-OVD was higher than that of Dispersive-OVD when injected through the cannula lumen and out of the tip. Therefore, the apparent viscosity of Cohesive-OVD near the cannula tip was about one-third lower than that of Dispersive-OVD. The shear rate of the Dispersive-OVD at the corneal endothelial surface during Cohesive-OVD injection was less than 10− 1– 10 s− 1, and the apparent viscosity was less than 30– 100 Pa∙s.Conclusion: Fluid dynamics simulation demonstrated how the soft shell technique works using two agents with different physical properties. The parameters obtained in this study provide useful metrics for understanding and predicting OVD behavior during eye surgery. Keywords: cataract surgery, chondroitin sulfate, hyaluronic acid, ophthalmic viscosurgical devices